Implementation of Posyandu and Posbindu for the Health and Welfare at Bintaos, Gunung Kidul - Yohana Citra Primandari; Maria Gwendoline Kartowiharjo Wasiono; Geovani Mario Amekae; Sonia Theresia Purba; Samuel Ananda Gemilang Saragih; Fajar Tarida Sibarani; Agatha Ellin Lourdhesta Wijaya; I Putu Gedhe Fernanda Farrel Diputra; Luios Andre; Diana Puspita Sari; Dinho Haratua Nainggolan; Puspitasari, Fransiska Hernina (Society : Jurnal Pengabdian Masyarakat, 2026)
The implementation of the Posyandu Balita (Integrated Health Services for Toddlers) and Posbindu Lansia (Integrated Health Services for the Elderly) in Padukuhan Bintaos, Sidoharjo, Tepus, Gunung Kidul, as part of a community service program during the Community Service Program (KKN), aimed to improve community health and welfare through integrated health services. The program included routine health check-ups, monitoring of toddlers' growth and development, nutritional education, promotion of a healthy lifestyle, and prevention of non-communicable diseases among the elderly. Activities were conducted using a participatory approach, involving local health cadres to ensure program sustainability. Post-program surveys and evaluations indicated increased community awareness of the importance of preventive healthcare, with participation rates of toddlers and elderly individuals reaching 85% of the target population. Posyandu Balita effectively identified and addressed early growth and development issues, while Posbindu Lansia improved elderly access to healthcare services. The program's success factors included collaboration with health cadres and educational approaches tailored to local community needs. These results suggest that consistent implementation of Posyandu Balita and Posbindu Lansia can serve as a strategic solution to enhance the quality of life in rural communities. However, challenges such as limited healthcare facilities and the need to improve cadre competencies must be addressed to optimize future implementations.